Die Neustrukturierung von Studiengängen "Deutsch als Fremdsprache" Probleme und Perspektiven Fachtagung 17.-19. November an der Universität Hannover - Casper-Hehne, Hiltraud; Koreik, Uwe; Middeke, Annegret (Universitätsverlag Göttingen, 2006)
The Bologna Process, whose objective is the creation of an "European Higher Education Area", should be concluded in 2010. In the last years the reactions ranged from total rejection over a more temporising attitude to clear and unambiguous affirmation. Hence, the "Fachverband Deutsch als Fremdsprache" (FaDaF - association for German as a foreign language) has accepted the challenge to enter on the level of science policy the discussion about the higher education structural reforms as far as the subject of German as a Foreign Language (DaF) is concerned. With the help of reports on the current situation and the future of the DaF degree programmes in various European countries, contributions regarding the crucial problems of the higher education structural reforms and a position paper about the curricular basis of the BA/MA degree programmes in the field of German as a foreign language, the basic parameters of the ongoing restructuring in this subject are discussed here.